Hydrobalneological methods in modern medical treatment - Kuliński, Włodzisław (Medical Studies/Studia Medyczne, 2015)
Introduction: Therapeutic methods combining balneology and hydrotherapy have been used in treatment and prevention for a long time. Their influence on the skin, based on mechanical, thermal, and hydrostatic stimuli, results in a reaction of the internal organs as well as the whole body. The most important effects of such procedures are changes within the cardiovascular system. Aim of the research: The use of hydrobalneological methods in modern medical treatment. Material and methods : The analysis focused on the influence of water jets at alternating temperatures in the treatment of functional cardiovascular disturbances with the use of non-invasive methods of autonomic nervous system function work-up based on the analysis of heart rate variability. The effect of the jets on heart rate and blood pressure was observed in 50 patients with first-degree hypertension, which was accompanied by radioelectrocardiographic (RECG) assessment of the influence of underwater massage and carbonic acid baths on the cardiovascular system in patients undergoing these procedures due to Da Costa’s syndrome. Results : Water jets at alternating temperatures successfully modulate the tension within the autonomic nervous system and stimulate its parasympathetic part. Underwater massage is a gentle procedure and does not cause significant changes in heart rate and RECG tracing. Carbonic acid baths decrease autonomic nervous system excitability. Conclusions: The study results show a possibility of regulating autonomic nervous system function with the use of selected balneological and hydrotherapeutic methods, and thus influencing the functional level of the human body which is most appropriate for the requirements created by the internal and external environment of the body.